Патогенетические механизмы фибрилляции предсердий и формирования предсердного фиброза = Pathogenic mechanisms of atrial fibrillation and atrial fibrosis formation - A. I. Gozhenko; N. R. Bayazitov; E. M. Levchenko; V. V. Goriachyi; A. V. Goriachyi (Kazimierz Wielki University, 2016)
Gozhenko A. I., Bayazitov N. R., Levchenko E. M., Goriachyi V. V., Goriachyi A. V. Патогенетические механизмы фибрилляции предсердий и формирования предсердного фиброза = Pathogenic mechanisms of atrial fibrillation and atrial fibrosis formation. Journal of Education, Health and Sport. 2016;6(10):22-33. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159538 http://ojs.ukw.edu.pl/index.php/johs/article/view/3921       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 07.10.2016.     УДК: 616.12-008.313.2-036.12-089:615.849   Патогенетические механизмы фибрилляции предсердий и формирования предсердного фиброза   А. И. Гоженко, Н. Р. Баязитов, Е. М. Левченко, В. В. Горячий, А. В. Горячий   Украинский научно-исследовательский институт медицины транспорта, Одесская Областная клиническая больница   Реферат Фибрилляция предсердий (ФП) является наиболее распространенной аритмией в клинической практике. Недавние экспериментальные исследования показали связь фибрилляции предсердий с застойной сердечной недостаточностью (ЗСН). В свою очередь ЗСН коррелирует с предсердным структурным ремоделированием заканчивающимся образование фиброза. Структурное ремоделирование является важным свойством субстрата ФП, продуцируя фиброз, который изменяет состав и функции предсердной ткани. Точные механизмы, лежащие в основе предсердного фиброза до конца не выяснены. Недавние экспериментальные и клинические исследования использующие анализ частотных характеристик показали, что ФП может быть характеризована с помощью отдельных стабильных, высокочастотных областей. Однако точный сигнальный процесс включенный в развитие предсердного фиброза на данный момент неизвестен.  Исследования проведенные на животных подтвердили важную роль систем, с участием TGFb1, ангиотензина II и связанных с ним медиаторов в распространении фиброза у пациентов с СН. Исследования проведенные на моделях мышей с гиперэкспрессией TGFb1 показали наличие глубокого предсердного фиброза и фибрилляцию предсердий при наличии нормального желудочкового миокара. Сердечная недостаточность в модели на собаках также продуцировала увеличение в предсердиях экспрессии TGFb1. Ингибирование его предотвращало предсердный фиброз и развитие субстрата для фибрилляции предсердий. В настоящем документе рассматриваются современные представления о том, как предсердный фиброз создает субстрат для ФП, обобщаются имеющиеся данные о механизмах, фиброза и его распространения, и освещаются терапевтические подходы, направленные на уменьшение структурного ремоделирования для предотвращения ФП. Ключевые слова: фибрилляция предсердий, фиброз, катетерная абляция, структурное ремоделирование   Pathogenic mechanisms of atrial fibrillation and atrial fibrosis formation   A. I. Gozhenko, N. R. Bayazitov, E. M. Levchenko, V. V. Goriachyi, A. V. Goriachyi   Ukrainian Scientific Research Institute of Transport Medicine, Odessa Regional Clinical Hospital   Abstract Atrial fibrillation (AF) is the most common cardiac arrhythmia in clinical practice. Recent experimental studies have shown an association of atrial fibrillation with congestive heart failure (CHF). In turn, CHF correlates with atrial structural remodeling resulted in the formation of fibrosis. Structural remodelling is an important property of AF substrate, producing fibrosis, which alters the composition and function of the atrial tissue. The exact mechanisms underlying atrial fibrosis has not been fully elucidated. Recent experimental and clinical studies using frequency analysis showed that AF may be characterized by a single stable, high-frequency areas. However, the exact process of the signal included in the development of atrial fibrosis is currently unknown. Studies on animals have confirmed the important role of systems involving TGFb1, angiotensin II and related mediators distributing fibrosis in patients with HF. This paper reviews the current understanding of how atrial fibrosis creates a substrate for AF, summarizes available data on the mechanisms of fibrosis and its distribution, and highlights the therapeutic approaches aimed at reducing the structural remodeling to prevent AF. Key words: atrial fibrillation, fibrosis, catheter ablation, structural remodeling     Патогенетичні механізми фібриляції передсердь і формування предсердного фіброзу   А. І. Гоженко, М. Р. Баязітов, О. М. Левченко, В. В. Горячий, О. В. Горячий   Український науково-дослідницький інститут медицини транспорту, Одеська Обласна клінічна лікарня   Фібриляція передсердь (ФП) є найбільш поширеною аритмією в клінічній практиці. Недавні експериментальні дослідження показали зв'язок фібриляції передсердь із застійною серцевою недостатністю (ЗСН).